Una nueva especie de Phoma agente causal de la "Mancha alquitranada del fresno americano" - Cordo, C.A.=700 1 Merlo, P.A.
(Es, En)
ilus., 8 ref.
Keywords: FRAXINUS PENNSYLVANICA; PHOMA; HONGOS; DEFOLIACION; MANCHAS; ESPAÑA; FRESNO; MANCHA FOLIAR